Development of maize (Zea mays) variety resistant to the maize stalk borer (Chilo partellus) - PANWAR, V P; MUKHERJEE, B K; SINGH, N N (The Indian Journal of Agricultural Sciences, 2013)
The resistant present in Antigua Gr I and double cross ’Colombian hybrid H 207’ was utilized as a source of resistance to develop maize (Zea mays L.) resistant to the maize stalk borer (Chilo partellus Swinhoe). As the insect resistance in maize is mainly under the influence of additive genes, the Population improvement procedure for breeding resistant maize variety was adopted which is more efficient to capitalise on the additive genetic component. The resistant genes of Antigua Gr I were super-imposed upon the resistant gene combination of’H 207’. Three cycles of half-sib and full-sib were followed and in each cycle the progenies were subjected to artificial infestation by the egg masses (black-head stage) of Chilo partellus. The progenies showing rating less than 5 on rating scale 1-9 were considered for further testing and incorporation. In this process, a balanced medium maturity (90-95 days) composite of selected families was derived and designated as entomological borer resistant (EBR) composite endowed with a good level of resistance and yield potential.